The unravelling: incest and the destruction of a family - Besel, Donna (The Regina collection, 2021)
"The brave retelling of the aftermath of reporting sexual assault in a small community. It's the antithesis of why a wedding should be memorable. In 1992, at a sister's nuptials, Besel's family members discovered that their father, Jock Tod, had molested their younger sister. As more survivors came forward, the family realized that their father had sexually assaulted four of the six sisters in a family of eleven children, and had been doing so for years. Despite there being enough evidence to charge their father, the trial and prosecution rocked Besel's family and deeply divided their small rural community. The Unravelling is a brave, riveting telling of the destruction caused by sexual assault, and the physical, psychological, emotional, financial, and legal tolls survivors often shoulder. Donna Besel offers an honest portrayal of the years-long process, from disclosure to prosecution, that offers readers greater insight into the challenges victims of sexual assault face and the remarkable strength and resilience required to obtain some measure of justice. Praise for The Unravelling 'Donna Besel's battle for acknowledgment of the evils that infected her childhood is illumined in The Unravelling by the sheer strength of her lucid, straightforward, voice. Besel carries us along an eye-opening journey, one of healing and remarkable endurance.'--Harriet Richards, author of Waiting for the Piano Tuner to Die"--